2018
DOI: 10.7717/peerj.5445
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolic profiling of sugarcane leaves induced by endophytic diazotrophic bacteria and humic acids

Abstract: Plant growth-promoting bacteria (PGPB) and humic acids (HA) have been used as biostimulants in field conditions. The complete genomic and proteomic transcription of Herbaspirillum seropedicae and Gluconacetobacter diazotrophicus is available but interpreting and utilizing this information in the field to increase crop performance is challenging. The identification and characterization of metabolites that are induced by genomic changes may be used to improve plant responses to inoculation. The objective of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 71 publications
4
47
0
2
Order By: Relevance
“…increasing electrolyte leakage, cell permeability and nutrient accumulation (David et al, 1994) and activating primary and secondary metabolism (Aguiar et al, 2018;Canellas et al, 2019). HA incubation upregulated genes responsible for cellular regulations in mock-inoculated plants, such as transcription factors, receptors and kinases, and altered the transcriptional response of tomato plants to endophytic bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…increasing electrolyte leakage, cell permeability and nutrient accumulation (David et al, 1994) and activating primary and secondary metabolism (Aguiar et al, 2018;Canellas et al, 2019). HA incubation upregulated genes responsible for cellular regulations in mock-inoculated plants, such as transcription factors, receptors and kinases, and altered the transcriptional response of tomato plants to endophytic bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…The protein metabolic pathways were activated by 32A in tomato roots in the HA condition, indicating the activation of nitrogen assimilation with upregulation of genes related to the metabolism of lysine, serine, glycine, cysteine, tyrosine, threonine, glutamine, alanine, arginine, and methionine. Likewise, the nitrogen and secondary metabolism was activated in H. seropedicae HRC54-inoculated tomato plants in the presence of HA (Olivares et al, 2015) and the increased concentration of amino acids and secondary metabolites was found in sugarcane plants inoculated with H. seropedicae HRC54 and G. diazotrophicus PAL 5 in the presence of HA (Aguiar et al, 2018;Canellas et al, 2019). In particular, 32A was able to fix atmospheric nitrogen in vitro (Campisano et al, 2014) and it caused the upregulation of a glutamine synthetase gene in tomato roots in the HA condition.…”
Section: Transcriptional Response Of Tomato Roots and Shoots To Two Omentioning
confidence: 93%
See 1 more Smart Citation
“…In sugar cane, the application of biostimulants such as humic acid to soil increased the concentration of metabolites involved in cellular growth. Ribonic acid was one such metabolite promoting cellular growth in sugar cane, 55 it can be suggested that in mango, ribonic acid may be involved in cellular growth and differentiation. D-Mannose was the monosaccharide identied at the earliest stage during the development of Chaunsa mango fruit, which is known to be a common metabolite between the two metabolic pathways, ascorbate biosynthesis pathway and the primary cell wall synthesis pathway, during tomato fruit development.…”
Section: Metabolic Proles Using Gc-ms Analysismentioning
confidence: 99%
“…The suitability of HA as an adjuvant to bacterial foliar sprays was demonstrated for field-grown maize, where yields were 65% higher than untreated controls and 40% higher than maize fields treated with HA or bacteria [27]. Moreover, a boost in the metabolic profile of sugarcane leaves induced by HA and PGPB [33] with activation of the glycolysis pathway and enhanced TCA activity resulted in the accumulation of α-ketoglutaric acid, which is a central metabolite in glutamine and glutamic acid synthesis. The stimulation of TCA enzymes by HS was previously reported by Nardi et al [34].…”
Section: Introductionmentioning
confidence: 99%